THE EFFECT OF VEGETABLE AND ANIMAL PROTEIN TYPES ON SATIETY LEVELS IN HEALTHY EARLY ADULT WOMEN - NARESWARI, ANNISA RAHMI (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Obesity is a dangerous health problem that many people suffer from. Hence, increasing the satiety on certain foods is one way to inhibit appetite after eating and control energy intake. Protein has the highest satiety among other macronutrients. The aim of this research is to determine the differences level of hunger, fullness, desire to eat, prospective food consumption (PFC), and energy ad libitum meal in young women after being given pant-based protein and animal protein. This research is an experimental method with a cross-over design. This study used a random sampling technique with 28 female participants with normal weight, BMI 21.6 ± 1.5 and aged 19-21 years. Data was collected by Visual Analogue Scale (VAS) questionnaire to collect data related to subjective indicators of satiety, which are hunger, fullness, desire to eat, and prospective food consumption (PFC). Objective indicators, macronutrient energy intake, are calculated through ad libitum meal. The results showed there are no significant differences in the indicators of hunger, fullness, desire to eat, and prospective food consumption (PFC). Energy intake of ad libitum meal in the plant-based protein group (337.9 ± 85.7) was lower than the animal protein group (367 ± 132.7) although there was no significant difference (p = 0.48). This study illustrates the acute effects on satiety level between plant-based protein and animal protein, and examines the postprandial effects. It is necessary to carry out research that examines the long-term effects of vegetable protein on weight management.